Kontribusi Daya Ledak Otot Tungkai dan Kelentukan Pergelangan Tangan terhadap Ketepatan Smash Bulutangkis - -, Antoni (FKIP Universitas Muhammadiyah Sukabumi, 2017)
This study aims to determine the explosive power of leg muscles, wrists formation, and know theircontribution to the accuracy of jumping smash badminton. The type of this research was correlational. The populationof this research is 54 people, the sample is taken by purposive sampling so that the sample is 25 people. Limb muscleexplosive power data obtained from a vertical jump, wrist shape by measuring wrist range, precision jumping smashtook smash accuracy test. Data were analyzed by using product moment correlation analysis and contribution (rÂ² x100%) with significance level Î± 0,05. Data analysis of explosive muscle limb power was obtained score = 0,4450 andtable = 0,396. Its contribution to the accuracy of jumping smash players is 18.14%. Data analysis of wrist formationwas obtained score = 0,5021 and table = 0,396. Its contribution to the accuracy of jumping smash is 23.31%.Analysis of explosive muscle limb power data and wrist joints together contributed 46.83% to the accuracy of jumpingsmash